Kompetensi Pedagogik: Sejauhmana Guru Geografi Memahami Hakikat Belajar pada Siswa? - Farkhan, Muhammad Robith; Suyanto, Suyanto; Yani, Ahmad (Universitas Pendidikan Ganesha, 2025)
Teachers need to understand the nature of student learning so that they can find a way of learning that is adjusted by considering various things. The gap in this study is that teachers are able to apply various learning strategies but do not yet understand the concept of the learning theory they use. This often causes a mismatch between the learning strategies used and the learning objectives to be achieved. This study aims to provide information related to the level of teacher understanding of the nature of learning as a form of pedagogical competence achievement. The researcher used a mixed research method consisting of a quantitative descriptive method through percentages, and a descriptive qualitative method through literature studies. The results of this study are several studies related to teacher understanding of the nature of learning are quite important in learning activities, some teachers still need to understand learning theory to practice it in class. It can be concluded that this study shows that the ability of teachers to understand the nature of student learning is still low which affects the teacher's pedagogical ability and efforts are needed to strengthen pedagogical competence.